2004
DOI: 10.1063/1.1639131
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational properties of one-dimensional ZnO:Ce nanostructures

Abstract: Different morphological one-dimensional ZnO:Ce nanostructures were synthesized on a large scale. The microstructures and vibrational properties were investigated by x-ray diffraction, electron microscopy, Raman spectroscopy, and infrared spectroscopy. The results show that Ce can effectively control the growth of ZnO nanostructures. The change of the morphology and local structure of ZnO under the influence of Ce results in the variation of vibrational properties. In Raman spectra of doped samples, some classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
78
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 21 publications
13
78
0
Order By: Relevance
“…5 shows that the relative intensity of LO and AM mode with respect to the E 2 ͑H͒ intensity increases almost linearly with effective Co concentration. Similar features around 500-600 cm −1 were observed in several works on TM, 18,[23][24][25] Ce, 26 and Sb-doped ZnO samples. 27 In those works the main peak of the broad band is, however, at ϳ530 cm −1 , and it has been attributed to complexes involving intrinsic defects, such as oxygen vacancies ͑V O ͒ and Zn interstitials ͑Zn i ͒.…”
Section: Resultssupporting
confidence: 64%
“…5 shows that the relative intensity of LO and AM mode with respect to the E 2 ͑H͒ intensity increases almost linearly with effective Co concentration. Similar features around 500-600 cm −1 were observed in several works on TM, 18,[23][24][25] Ce, 26 and Sb-doped ZnO samples. 27 In those works the main peak of the broad band is, however, at ϳ530 cm −1 , and it has been attributed to complexes involving intrinsic defects, such as oxygen vacancies ͑V O ͒ and Zn interstitials ͑Zn i ͒.…”
Section: Resultssupporting
confidence: 64%
“…The small shifting of E 2 phonon mode can be related to a strain induced by Fe dopant. Same phenomenon occurred in Ce and Tb doped ZnO samples reported in literature [19,20]. When the size of particles reduces to nanoscale, the k = 0 selection rule for the first order Raman scattering is relaxed and the phonon scattering will not be limited to the centre of Brillouin zone.…”
Section: Raman Spectroscopymentioning
confidence: 53%
“…It has been reported that the interaction between electromagnetic ͑EM͒ radiation and the particles depends on the size, shape, and state of aggregation of the crystal. 21 Since the particle size in this study is much lower than the EM radiation, surface phonon modes ͑SPM͒ can be observed in the IR spectra as well. For spherical particles, the value of the first order ͑n =1͒ SPM is given by 25 …”
Section: Ftir Spectroscopy Studymentioning
confidence: 98%
“…The IR active optical phonon modes of ZnO show a characteristic broad reststrahlen band in the spectral range of 300-600 cm −1 . 21 Higher wave number peaks correspond to vibration modes of various impurities such as hydroxyl, carboxylate, and alkane in the materials. 22 In this work, within the displayed frequency range, phase segregated ZnMgO and ZnCdO alloy nanostructures show two impurity bands near 600-1000 cm −1 due to C-OH bond.…”
Section: Ftir Spectroscopy Studymentioning
confidence: 99%